المسؤولية الدولية عن العمل غير المشروع دوليا وفق تصورات لجنة القانون الدولي - جواد حدادي; كمال ستيتي (My University, 2025)
Through our study of the theme of international responsibility for internationally wrongful acts according to the vision of the International Law Commission, we have attempted to address the theoretical aspect of this and to explain how to apply it concretely using the deductive analytical method. In the first chapter, we focused on the conceptual framework of international responsibility. We defined it as a legal system imposing sanctions or obligations on the State in the event of a violation of its obligations stipulated in international law, arising from international treaties and customs, as well as well as other sources. As stipulated in Article 38 of the Statute of the International Court of Justice, the provisions of which were incorporated in the 2001 draft, we have also addressed the internationally wrongful act as a legal basis for the establishment of international responsibility, which requires two conditions for its establishment: that the act be in violation of an international obligation, and that it be proven that it is attributed to the State. In the second chapter, we discussed the effects of international responsibility, which is reflected in the agreement of the State that committed the act. internationally wrongful act and its commitment not to repeat it. The injury is repaired by reparation of the damage caused, either by restoring the initial situation or by just material compensation. We have also explained the legitimate means to which the injured State can resort in this context Controls of international law. In the second section, we discussed the cases of exemption from international responsibility, provided for exceptionally by the International Law Commission in the draft, as well as the case of necessity. These cases exonerate a State from its international responsibility despite the commission of an internationally wrongful act. .......................... من خلال دراستنا لموضوع المسؤولية الدولية عن العمل غير المشروع دولي وفق رؤية لجنة القانون الدولي، أين حاولنا التطرق إلى الجانب النظري منه، وبيان كيفية تطبيقاته العملية باستعمال المنهج الاستدلالي التحليلي. ففي الفصل الأول ركزنا على الإطار المفاهيمي للمسؤولية الدولية،فقمنا إلى تعريفها باعتبارها نظام قانوني يرتب جزاءات أو التزامات على الدولة نتيجة مخالفتها لالتزاماتها المقررة وفق القانون الدولي والتي مصدرها المعاهدات والأعراف الدولية، وباقي المصادر المنصوص عليها في المادة 38 من النظام الأساسي لمحكمة العدل الدولية، والتي تم تعين أحكامها في مشروع 2001 ، كما تناولنا العمل غير المشروع دوليا، باعتباره الأساس القانوني لقيام المسؤولية الدولية والذي يتطلب شرطان لقيامه، وهو أن يكون الفعل مخالفا لالتزام دولي، وان يثبت إسناده للدولة. أما في الفصل الثاني، فقد تطرقنا إلى اثأر المسؤولية الدولية، والتي تتمثل في اتفاق الدولة التي أقدمت إلى ارتكاب الفعل غير المشروع دوليا، والتزامها بعدم تكراره، تم جبر الضرر عبر إصلاح الأضرار التي ارتكبتها أما بإعادة الحال إلى ما كانت عليه، أو تقديم تعويض مادي منصف،كما بيننا الأساليب المشروعة التي يمكن أن تلجا إليها الدولة المتضررة ضمن ضوابط القانون الدولي. وفي المبحث الثاني، تطرقنا إلى حالات الإعفاء من المسؤولية الدولية، والتي تم النص عليها استثنائيا من طرف لجنة القانون الدولي في المشروع وحالة الضرورةـ وهذه الحالات تعفي الدولة من تحمل المسؤولية الدولية رغم ارتكابها للعمل غير المشروع دوليا. ............................. À travers notre étude du thème de la responsabilité internationale pour fait internationalement illicite selon la vision de la Commission du droit international, nous avons tenté d’aborder l’aspect théorique de celui-ci et d’expliquer comment l’appliquer concrètement en utilisant la méthode analytique déductive. Dans le premier chapitre, nous nous sommes concentrés sur le cadre conceptuel de la responsabilité internationale. Nous l'avons définie comme un système juridique imposant des sanctions ou des obligations à l'État en cas de violation de ses obligations stipulées en droit international, découlant des traités et coutumes internationaux, ainsi que d'autres sources. Comme le stipule l’article 38 du Statut de la Cour internationale de Justice, dont les dispositions ont été reprises dans le projet de 2001, nous avons également abordé le fait internationalement illicite comme base juridique pour l’établissement de la responsabilité internationale, laquelle requiert deux conditions pour son établissement : que le fait soit en violation d’une obligation internationale, et qu’il soit prouvé qu’il est attribué à l’État. Dans le deuxième chapitre, nous avons abordé les effets de la responsabilité internationale, qui se traduit par l'accord de l'État auteur du fait internationalement illicite et son engagement à ne pas le répéter. Le préjudice est réparé par la réparation des dommages causés, soit par le rétablissement de la situation initiale, soit par une juste compensation matérielle. Nous avons également expliqué les moyens légitimes auxquels l'État lésé peut recourir dans ce contexte Contrôles du droit international. Dans la deuxième section, nous avons abordé les cas d'exonération de responsabilité internationale, prévus à titre exceptionnel par la Commission du droit international dans le projet, ainsi que le cas de nécessité. Ces cas exonèrent un État de sa responsabilité internationale malgré la commission d'un fait internationalement illicite.
Keywords: Keywords: International responsibility – Internationally wrongful act – 2001 draft of the International Law Commission relating to international responsibility.; الكلمات المفتاحية : المسؤولية الدولية – الفعل غير المشروع دوليا – مشروع 2001 للجنة القانون الدولي المتعلق بالمسؤولية الدولية .; Mots-clés : Responsabilité internationale – Fait internationalement illicite – Projet de 2001 de la Commission du droit international lié à la responsabilité internationale.